Changing patterns of electricity use in European manufacturing: A decomposition analysis - Lars Wenzel; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
This paper sets out to investigate the changing patterns of electricity intensity in European manufacturing for the time span 2000-2011. While GVA in Manufacturing has grown and electricity use has declined, it is not clear that this decrease in intensity is directly associated with improvements in technology. Decomposition of the effect suggests that a switch towards less energy intensive sectors accounted for roughly 10% of the total change in electricity intensity. A further level of disaggregation was added in order to account for the factor mix in the form of potential substitution between labor and electricity. The factor mix effect was largely positive, implying that substitution from labor to electricity has been the norm. The average decrease in labor intensity has been more pronounced than the corresponding decrease in electricity intensity. Accordingly, aggregate changes cannot purely be attributed to less electricity-dependent modes of production, but are rather due to general improvements in productivity. Interestingly, this does not appear to be driven by factor prices, as electricity prices grew significantly more than wage compensations within the period at hand. – – Diese Arbeit untersucht zeitliche Veränderungen der Stromintensität in der europäischen Industrie in der Zeitspanne 2000 bis 2011. Parallel zur steigenden industriellen Produktion ist der Stromverbrauch der Industrie im Mittel gesunken, dies ist jedoch nicht zwangsläufig das Ergebnis von technologischem Fortschritt. Eine Zerlegung in Struktur- und Intensitätskomponente ergibt, dass etwa 10 % der gesunkenen Stromintensität auf sektorale Effekte zurückzuführen sind. Um zusätzlich Änderungen im Substitutionsverhältnis von Arbeit und Energie zu berücksichtigen, wurde in einem weiteren Zerlegungsschritt ein Faktormixeffekt bestimmt. Dabei wurde im allgemeinen ein systematischer Anstieg des Arbeitseinsatzes in Relation zum Stromverbrauch festgestellt. Änderungen in der Intensität können damit nicht allgemein auf einen Wechsel zu weniger stromabhängigen Produktionsmethoden zurückgeführt werden. Interessanterweise schien dies nicht durch Änderungen in den Faktorpreisen verursacht worden zu sein, da die Strompreise deutlich stärker gewachsen sind als die Löhne.
Keywords: 330; decomposition analysis; electricity intensity; European manufacturing; Logarithmic Mean Divisia Index (LMDI)